2023
DOI: 10.1097/phm.0000000000002377
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Repetitive Transcranial Magnetic Stimulation (HF-rTMS) on Overall Cognition in patients with Post-Stroke Cognitive Impairment: A Systematic Review and Meta-analysis

Xin Chen,
Huoqin Xiu,
Yufei Hou
et al.

Abstract: Objective To comprehensively assess the recovery effects of high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) in patients with post-stroke cognitive impairment (PSCI). Methods Six English and four Chinese databases were searched for relevant studies published up to January 2022. Randomized controlled trials (RCTs) of patients with PSCI treated with HF-rTMS were included. Included studies were assessed for the risk of bias through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…MMSE, MoCA, BI, MBI, RBMT, and LOTCA were among the primary outcome indicators used. Thirteen ( 31–41 , 43 , 47 ) articles reported financial support. Most studies concluded that rTMS has advantages in treating PSCI but emphasized the need for more, higher-quality studies to validate the results.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…MMSE, MoCA, BI, MBI, RBMT, and LOTCA were among the primary outcome indicators used. Thirteen ( 31–41 , 43 , 47 ) articles reported financial support. Most studies concluded that rTMS has advantages in treating PSCI but emphasized the need for more, higher-quality studies to validate the results.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the literature rankings published in 2023 were positioned as 17. The earliest publication date is 2021, containing five ( 31 , 33 , 34 , 42 , 46 ) studies; the latest is 2023, containing 10 ( 32 , 36–40 , 43–45 , 47 ). Meanwhile, there were two ( 35 , 41 ) studies in 2022.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations